2011
DOI: 10.1590/s0103-507x2011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da experiência de dor pós-operatória em pacientes de unidade de terapia intensiva

Abstract: Evaluation of postoperative pain experience in intensive care unit patients Avaliação da experiência de dor pós-operatória em pacientes de unidade de terapia intensiva

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
8
0
10
Order By: Relevance
“…This care practice is part of pressure ulcer prevention, which has implications for patients' prognosis and outcome and impact on hospitalization costs, which corroborates a study that found an increase in the length of hospital stay by approximately 6% among patients with pressure ulcers. (18,19) Regarding patient identification, medications used, and fall prevention, the item "clean, dry limb restraint without arm and leg circulation restriction" obtained a relatively high level of significance when the ICUs were compared (p<0.01). Studies show that nurses, as members of the multidisciplinary team and leaders of the nursing team in the ICU, should develop safe and effective ways to provide care.…”
Section: Discussionmentioning
confidence: 99%
“…This care practice is part of pressure ulcer prevention, which has implications for patients' prognosis and outcome and impact on hospitalization costs, which corroborates a study that found an increase in the length of hospital stay by approximately 6% among patients with pressure ulcers. (18,19) Regarding patient identification, medications used, and fall prevention, the item "clean, dry limb restraint without arm and leg circulation restriction" obtained a relatively high level of significance when the ICUs were compared (p<0.01). Studies show that nurses, as members of the multidisciplinary team and leaders of the nursing team in the ICU, should develop safe and effective ways to provide care.…”
Section: Discussionmentioning
confidence: 99%
“…No paciente hospitalizado, o controle e alívio da dor são de responsabilidade do profissional de saúde, que muitas vezes, devido à preocupação com os eventos adversos provocados pelos analgésicos, acabam por subtratar os pacientes (3) . Os métodos de controle e de avaliação da dor são amplos e envolvem a aquisição de diversas informações relacionadas ao início da dor, à localização, à intensidade, à duração e à periodicidade dos episódios dolorosos, às qualidades sensoriais e afetivas do paciente e aos fatores que iniciam, aumentam ou diminuem a sua intensidade (4) . Entre os profissionais de saúde, em um estudo realizado no ano de 2010, exalta-se o papel do enfermeiro no gerenciamento da dor, enfatizando atividades como: explorar e valorizar a queixa de dor; coletar dados sobre fatores agravantes, antecedentes pessoais e familiares; investigar o desconforto causado pela dor; e utilizar-se de instrumentos que podem auxiliar na sua mensuração e avaliação, intervindo de maneira eficaz na qualidade da analgesia (1) .…”
Section: Introductionunclassified
“…Cienc Cuid Saude 2017 Out-Dez; 16 (4) Organization (JCAHO) destaca como sendo obrigatório no processo de acreditação hospitalar. A JCHAO nos chama atenção na observação dos benefícios no cuidado da dor nas instituições hospitalares, não só por minimizar e eliminar o desconforto, mas também por facilitar a recuperação, evitar efeitos adversos relacionados e promover tratamento com baixos custos.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Os cuidados despendidos a pacientes críticos estão cada vez mais aprimorados e visam, não apenas, aumentar a sobrevida e permitir que os indivíduos possam ter uma reintegração social, como em alguns casos proporcionar o mínimo desconforto possível durante a permanência no ambiente hospitalar [1,2]. Um paciente é considerado crítico quando há risco iminente de vida por instabilidade hemodinâmica ou pelo déficit de função de um órgão ou sistema do organismo, necessitando de cuidado clínico imediato [3,4].…”
Section: Introductionunclassified